Analisis Dampak Bank Sampah Induk New Normal Terhadap Kenaikan Ekonomi Bagi Masyarakat Di Tanjung Sari, Simpang Selayang - Nanda, Meutia; Claudia, Cindy; Sadia, Halima; Utami, Ajeng Putri; Addini, Nafisah Nur; Rafif, M. Khaiyir; Ihza, Uday (Jurnal Ilmiah Wahana Pendidikan, 2023)
Garbage is an environmental and urban community problem that until now has no solution. Limited Garbage Disposal Sites (TPA) in Medan City, making this waste problem even more complex. The waste bank is an alternative in the waste management strategy. The waste bank is one of the programs that can change the pattern of people's views on waste management. Some of the problems that exist with partners include: Partners have basic problems such as lack of knowledge about the dangers of waste & waste management/sorting and lack of knowledge about waste banks, how they work, and generate income just by sorting and depositing them to the waste bank. The approach method that will be used is socialization about waste and its management, and how housewives can earn income from existing waste management. The expected output target is that the community is educated to sort waste and deposit waste into the Garbage Bank, so as to create a clean and healthy environment. It is hoped that the role of the Village Government will be in establishing this waste bank.